2018
DOI: 10.1038/s41416-018-0211-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite and lipoprotein responses and prediction of weight gain during breast cancer treatment

Abstract: BACKGROUND: Breast cancer treatment has metabolic side effects, potentially affecting risk of cardiovascular disease (CVD) and recurrence. We aimed to compare alterations in serum metabolites and lipoproteins during treatment between recipients and nonrecipients of chemotherapy, and describe metabolite profiles associated with treatment-related weight gain. METHODS: This pilot study includes 60 stage I/II breast cancer patients who underwent surgery and were treated according to national guidelines. Serum samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
1
16
0
1
Order By: Relevance
“…GSEA results showed that butanoate metabolism was highly enriched in high immune infiltration. The change of butanoate metabolism in breast cancer patients receiving chemotherapy [ 36 ]. Changes in metabolic pathways may affect the fate of immune cells to regulate immunity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSEA results showed that butanoate metabolism was highly enriched in high immune infiltration. The change of butanoate metabolism in breast cancer patients receiving chemotherapy [ 36 ]. Changes in metabolic pathways may affect the fate of immune cells to regulate immunity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different chemotherapy regimens have been shown to exert alterations in normal lipid metabolism possibly via mechanisms involving oxidative stress and inflammation [25], [26], [27]. Regarding the effects of anti-VEGF agents, Joerger (2010) described previously in a case report a breast cancer patient whose chemotherapy-induced hyperlipoproteinemia persisted until the cessation of monoclonal VEGF-inhibitor bevacizumab [28].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, alterations of HDL, LDL, VLDL cholesterols and triglycerides were observed during and after treatments. These observations were hypothesized to be related to inflammation processes and lipids homeostasis [ 107 , 117 ].…”
Section: Nmr Metabolomics Of Blood Plasma/serummentioning
confidence: 99%